Effect of welding parameters on the microstructure and mechanical properties of linear friction welded Ti-6.5Al-3.5Mo-1.5Zr-0.3Si joints. (October 2019) - Wang, Xinyu; Li, Wenya; Ma, Tiejun; Yang, Xiawei; Vairis, Achilles
Highlights: A sound LFW joint cannot be obtained at a relatively low shear velocity. Increasing friction pressure can refine the grains in welds effectively. The texture evolution mechanism in welds by various welding parameters was clarified. The relationship among parameters, microstructure and properties was obtained. Abstract: An extensive investigation on the effect of linear friction welding parameters on the microstructure, texture distribution and mechanical properties of Ti-6.5Al-3.5Mo-1.5Zr-0.3Si titanium alloy joints was performed. Results indicate that a critical shear velocity is necessary to be reached to obtain a sound joint. The width of the thermomechanically-affected zone (TMAZ) was reduced with friction pressure or/and shear velocity, while the width of the weld center zone (WCZ) remained constant. In WCZ, a microstructure of recrystallized β grains with acicular α laths was formed, and the grain size became smaller with friction pressure. Electron back scattered diffraction was carried out to analyze the texture development with welding parameters. With the increase in friction pressure, the intensity of 112<111 > β texture increased; in the case of α texture, the intensity of T texture increased while decreased for the rest. By examining mechanical properties, strong relationships between maximum hardness and β grain size, as well as between joint elongation and PAZ width, were identified.